Multiple adoption: four children for a big family (Journal of Parents and Teachers, 2014)
In this article, a family portrays their experience as marriage seeking children and their testimony as a family with four adopted children. It is explained that adoptive children are also the fruit of the love of the spouses, just as it is the fruit of love to move from a family of two members to a large one.
Keywords: Family; adoption; love.